It is written--scripture citing scripture: essays in honour of Barnabas Lindars, SSF - Carson, D.; Williamson, H.; Lindars, Barnabas (Cambridge University Press, 1988)
This festschrift aims both to survey and advance research on the use of the Hebrew Scriptures within the Bible as a whole. An international team of scholars, chosen for their expertise as well as their association with Barnabas Lindars, cover between them the major divisions of the Old Testament and Intertestamental literature as well as the writings of the New Testament. The work thus makes a contribution to such areas of interest as midrash, apocalyptic, a developing understanding of canon, the nature of prophecy and fulfilment and the literary genres used by biblical writers. It should be of interest to a broad spectrum of students and scholars of theology as well as clergy.